الكشف عن بعض عناصر المعادن الثقيلة في لحوم ومنتجاتها مصنّعة محلّياً أو مستوردة - المصري, محمد; رحمه, سها (Latakia University Journal -Biological Sciences Series, 2013)
أجريت هذه الدراسة لتحديد مستوى المعادن الثقيلة ( الرصاص, الكادميوم, الزئبق, النيكل,النحاس, الحديد, الزنك) في اللحوم المصنّعة المحلّية والمستوردة الآتية:السردين (الكامل المعلب) ولحم سمك التونة (الشريحة المعلبة ) وسمك الهامور(الكامل المجمد) والسمك الفراتي (الكامل المجمد) والسمك (الكامل المجمد) انتاج بحيرة قطينة في سوريا ولحم الغنم (الشريحة المجمدة) ولحم البقر(الشريحة المجمدة) ونقانق الغنم (الكاملة المجمدة) ونقانق البقر (الكاملة المجمدة) والنقانق (المحشية المجمدة) انتاج هولندا وكبد الغنم (الكامل المجمد) وكبد الدجاج المسمّن (الكامل المجمد) ولحم الدجاج المسمّن (الكامل المجمد) ومرتديلا الدجاج (المعلبة) ومرتديلا البقر(المعلبة) ومرتديلا الدجاج (المعلبة) انتاج هولندا. حُدّدت تراكيز المعادن الثقيلة في عينات اللحوم المصنّعة المدروسة بجهاز الامتصاص الذري. فكانت التراكيز على أساس الوزن الرطب مقدرة (ppm) على النحو التالي: راوحت قيم الرصاص (5.61 – 0.1 ), والكادميوم (2.02 – 0.01), والزئبق (79.01– 0.14),والنيكل (0.82 – 0.11), والنحاس (0.24–(6.89 , والحديد (91.03 – 1.01), والزنك (45.5– 8.14), أظهرت النتائج أن مستويات الرصاص والكادميوم والزئبق والنيكل أعلى من الحدود المسموح بها بحسب منظمة الصحة العالمية(WHO) ومنظمة الأغذية والزراعة الفاو (FAO ) في بعض عينات اللحوم المصنّعة المدروسة المحلّية والمستوردة, على حين كانت تراكيز النحاس والحديد والزنك أدنى من المستويات المسموح بها. This study was conducted to identify the levels of heavy metals (lead, cadmium, mercury, nickel, copper, iron, zinc) in the following processed local and imported meat: Sardine (canned full), Tuna (canned chunks), Hammour (frozen full), Euphrates Fish (frozen full), fish produced at Qattinah Lake in Syria (frozen full) , lamb (frozen ground), beef (frozen ground), lamb sausage (frozen full), beef sausage (frozen full), sausageproduced in Netherlands (frozen stuffed), lamb liver (frozen full), broiler chicken liver (frozen full), broiler chicken (frozen full), chicken mortadella (canned), beef mortadella (canned), chicken mortadella (canned) produced in Netherlands. Heavy metal concentrations were identified in the samples of the studied meat by atomic absorption spectrometer. The concentrations taken in the wet weight measured in (ppm) were as follows: lead values range between (0.1–5.61),cadmium(0.01–2.02), mercury (0.14 –79.01), nickel (0.11 - 0.82), copper (0.24 – 6.89), iron (1.01 - 91.03), zinc (8.14 - 45.5). It was noticed that in some of the studied samples of the imported and locally-processed meat the levels of lead, cadmium, mercury, and nickel were above the levels permitted by WHO (World Health Organization) and by FAO (Food and Agriculture Organization).While the concentrations of copper, iron, and zincwere belowthelevels permitted.